Longitudinal study of perceived negative impact in African American and Caucasian mothers of children with autism spectrum disorder. (July 2013) - Carr, Themba; Lord, Catherine
The purpose of this study was to examine the stability of mothers' perceptions of the negative impact of having a child with ASD in a sample of African American and Caucasian families as their children transitioned to early adolescence. Participants were mothers and children participating in an ongoing longitudinal study of children referred for diagnosis of ASD at age two. Analyses included data from two time points, when child participants were approximately 9 and 14 years old. Linear mixed model analyses were used to examine the relationship between the primary outcome variable, mothers' perceived negative impact across time, and hypothesized predictors. Negative impact increased significantly from late childhood to into adolescence. However, African American mothers with lower education reported significantly lower levels of perceived negative impact at both time points. Findings show that for some families, the transition to adolescence is a period in which mothers experience increased amounts of negative impact and highlight the importance of examining the influence of socioeconomic variables. Furthermore, data suggest that there may be cultural differences mediating the relationship between maternal education, ethnicity, and perceived negative impact. Implications for the importance of including families from varying levels of socioeconomic status in ASD research are discussed.